2012
DOI: 10.1021/nl204388p
|View full text |Cite
|
Sign up to set email alerts
|

Graphite Nanoplatelets and Caenorhabditis elegans: Insights from an in Vivo Model

Abstract: We evaluated the toxicity of graphite nanoplatelets (GNPs) in the model organism Caenorhabditis elegans. The GNPs resulted nontoxic by measuring longevity as well as reproductive capability end points. An imaging technique based on Fourier transform infrared spectroscopy (FT-IR) mapping was also developed to analyze the GNPs spatial distribution inside the nematodes. Conflicting reports on the in vitro antimicrobial properties of graphene-based nanomaterials prompted us to challenge the host-pathogen system C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(113 citation statements)
references
References 32 publications
(48 reference statements)
3
109
0
Order By: Relevance
“…[19][20][21] These NMs include metal nanoparticles (NPs; TiO 2 , Al 2 O 3 , and ZnO 2 ) [22][23][24] and carbon NPs (carbon NTs [CNTs], graphene oxide [GO], and graphite nanoplatelets). [25][26][27][28] Here, we analyze the two aforementioned representative forms of BN NMs in C. elegans: BNNSs and BN-800-2. In this study, we examined the multiple phenotypic toxicities of two types of BN NMs with different morphology, size, and solubility using C. elegans in aqueous media.…”
Section: Wang Et Almentioning
confidence: 99%
“…[19][20][21] These NMs include metal nanoparticles (NPs; TiO 2 , Al 2 O 3 , and ZnO 2 ) [22][23][24] and carbon NPs (carbon NTs [CNTs], graphene oxide [GO], and graphite nanoplatelets). [25][26][27][28] Here, we analyze the two aforementioned representative forms of BN NMs in C. elegans: BNNSs and BN-800-2. In this study, we examined the multiple phenotypic toxicities of two types of BN NMs with different morphology, size, and solubility using C. elegans in aqueous media.…”
Section: Wang Et Almentioning
confidence: 99%
“…Graphite has also been widely considered as benign for various biomedical use. [ 16 ] Initially, bare carbon ink was prepared by thoroughly dissolving 30 wt% graphite in PEG solution (60 wt% in water). It was observed that higher graphite or PEG content led to clogging of the pen.…”
Section: Rationale For Enzymatic-ink Compositionmentioning
confidence: 99%
“…Here a primary imaging method based on Fourier transform infrared spectroscopy (FTIR) mapping has already been preferentially exploited in structural elucidation to investigate the probable interplays and complicated interactions between ALA and lipids during the course of preparation of ALA-NLC aqueous dispersion (Zanni et al, 2012). The method has obtained significant importance in the near future since it allows the occasion to completely comprehend the configuration of biological molecules (Palaniappan et al, 2011).…”
Section: Qualitative Features Of the Ftir Spectra Of The Nlc Systemmentioning
confidence: 99%